The Effectiveness of Ear Acupuncture Therapy and Bloodletting Apex in Lowering Blood Pressure for Patients with Hypertension in Ngampon Hamlet, Mojosongo Village - Diah Mahardewi, Ni Made; Badri, Sholichan; Prasetya, Hanung (Indonesian Journal of Acupuncture, 2024)
High blood pressure is a disease caused by disorders in the blood circulation system where systolic blood pressure is higher than 140 mmHg and diastolic blood pressure is higher than 90 mmHg. This research aims to determine the effectiveness of ear acupuncture therapy and ear apex bloodletting in reducing blood pressure in patients with high blood pressure in Ngampon Village. The research was conducted from November 2018 to April 2019 in Ngampon Village, Mojosongo Sub-district, Surakarta City. This study involved a sample of 32 subjects who met the inclusion and exclusion criteria (males: 14 and females: 18). The research design was pre-experimental with a one-group pretest-posttest design. Data was collected through interviews/anamnesis and blood pressure observation before and after the intervention. The Wilcoxon test results yielded a p-value of 0.000 < α = 0.05, indicating a decrease in blood pressure after the ear acupuncture therapy and ear apex bloodletting intervention. Ear acupuncture therapy and ear apex bloodletting effectively reduce blood pressure in patients with high blood pressure.